Agroforestry research in India - SOLANKI, K R (The Indian Journal of Agricultural Sciences, 2013)
Agroforestry practice in India is old and traditional. Some systems have been researched since the late 19th century and there has been research on fodder-fuel plantations since the 1950’s. Different agroforestry practices in India under different agro-ecological regions arc described here with research results. It is concluded that there are several areas of research on agroforestry)’ yet to be untouched. Some of the systems are well described. There is need of greater research on practice. The agroforestry research endeavour so far, apart from indicating possibilities for increased production of foodgrain, fodder and fuel, the system still needs greater research and management. The challenges and opportunities for improvement are vast.